Using PVA, Methacrylate And Lauroyl Chitosan As Separator In Supercapacitors. - M. A. Hashim; Lawal Sa’adu; Masbudi bin Baharuddin; Karsono A. Dasuki (Canadian Center of Science and Education, 2024)
Volume: 3 No: 1 (page: 25-29)